A primary pure pancreatic-type acinar cell carcinoma of the stomach: a case report. Issue 1 (December 2017) - Kim, Kyoung; Kim, Chan; Hong, Seung-Mo; Jang, Kyu
Abstract Background Acinar cell carcinoma represents only 1–2% of exocrine pancreatic neoplasms. On exceptionally rare occasions, primary acinar cell carcinoma can occur in ectopic locations. Herein, we report a case of pure pancreatic-type acinar cell carcinoma arising in the stomach. Case presentation A 54-year-old male presented with a gastric submucosal mass detected by endoscopic examination. Laparoscopic wedge resection was performed. Macroscopically, the 2.7 cm yellowish mass was located in the submucosa of the stomach. Microscopically, the tumor was well circumscribed and had a homogeneous acinar architecture. The tumor cells were small and had a minimal amount of cytoplasm. The nuclei of the tumor cells were round to oval with finely dispersed chromatin. The tumor cells were strongly positive for α1-antitrypsin, chymotrypsin, and α1-antichymotrypsin immunostaining, consistent with pancreatic exocrine differentiation. There was no clinical or radiologic evidence of primary pancreatic or head and neck tumors. After surgical resection of the tumor, there was no recurrence or metastasis during 33 months follow-up. Conclusion In this report, we have presented a rare case of primary pure pancreatic-type acinar cell carcinoma arising in the stomach and suggest that it could be helpful if the pathologist were aware that pancreatic-type acinar cell carcinoma could arise in the stomach as a polypoid submucosal tumor in the routine diagnostic field of gastric endoscopy.